(untitled) (Revista Contexto & Saúde, 2026)
Objective: to analyze the spatial distribution and behavior of drug-resistant tuberculosis in the state of Paraná, from the perspective of incidence, temporal trends, and its relationship with Brazil’s border region with other countries. Method: ecological study with spatial and temporal analysis. Data were collected from the Special Tuberculosis Treatment Information System and the Department of Informatics of the Unified Health System. New cases of drug-resistant tuberculosis reported in Paraná between 2013 and 2020 were included. The incidence rate was calculated, followed by the Spatial and Space-Time Scan Statistics technique, and temporal regression analysis using the Joinpoint technique. Results: 515 cases of drug-resistant tuberculosis were reported during the study period, with an incidence of 15.76 cases/100,000 inhabitants, identifying risk areas in the North, East, and West regions of the state. Space-time analysis identified, in the East region, a cluster with the highest relative risk (RR = 9.89) for the period from 2013 to 2016. In the temporal trend, it was found that drug-resistant tuberculosis cases decreased from 2020 onwards. Conclusion: it is interesting to note that, in this study, drug-resistant tuberculosis did not demonstrate a direct relationship with this region. However, spatial analysis of incidence and the identification of clusters with high rates and risks provided an overview of cases in the state. Given this scenario, it is essential to invest in prevention, diagnosis, and treatment strategies to reduce the burden of resistant bacilli and achieve the proposed goals for tuberculosis eradication.